Recognition of ecosystem-based management principles in key documents of the seabed mining regime: implications and further recommendations. (26th December 2020) - Guilhon, Maila; Montserrat, Francesc; Turra, Alexander
Abstract: New human uses on the marine environment, such as deep-sea mining (DSM), have necessitated the adoption of more holistic approaches such as ecosystem-based management (EBM) to secure sustainable development. The United Nations Convention on the Law of the Sea (UNCLOS) and the rules, regulations, and procedures adopted by the International Seabed Authority (ISA) represent the main regulatory framework to govern DSM activities. This study aimed to examine whether UNCLOS and ISA documents include references to EBM principles, and if these references vary in documents through time. Following a literature review, 26 EBM principles were collated into 8 general categories, and their adherence to 5 key documents related to the DSM regime was analysed. Results demonstrated a trend in recognizing EBM principles in documents over time, especially in the Draft Regulations for Exploitation. However, the mere recognition of EBM principles in the regulatory framework does not guarantee that the approach will be clearly understood and appropriately incorporated by contractors throughout the process. For such, further clarification on the meaning of the Ecosystem Approach in the DSM context and building the capacity of the ISA Legal and Technical Commission are among the recommendations presented by this study.